PENGEMBANGAN MEDIA PEMBELAJARAN PUZZLE IKATAN KOVALEN (PETALEN) KELAS X DI SMA NEGERI 2 SUNGAI RAYA - Nova Miola Anggreini; Fitriani Fitriani; Dedeh Kurniasih (Jurnal Ilmiah Ar-Razi, 2019)
The students problem in understanding the covalent bonds was caused by the ineffective learning instructional media which is used by the teacher didn’t fit the student’s characteristic. Therefore, it is important to develop instructional media of Petalen for covalent bonds class. The validation of the media is validated in three aspects. They were validity from the results of the game, practicality from the results of the questionnaire, and the effectiveness from the results of the pre and post tests. This study used a Research and Development (R & D) model of Borg and Gall conducted in seven stages. The study showed that instructional media of Petalen was suitable for teaching learning process. It can be seen from the results of the material and media aspects by 1,00 and 1,00 which were valid. The results of the practicality of the questionnaires on the small and main tryouts were 94,55% and 92,81% and were considered practical. The results of the effectiveness of the N-Gain on the small and main tryouts were 0,77 and 0,66 (high category). Therefore, instructional media of Petalen was valid and effective. It is suitable to be used as the learning instructional media in Chemistry class.